Toward a Nonspeech Test of Auditory Cognition: Semantic Context Effects in Environmental Sound Identification in Adults of Varying Age and Hearing Abilities. - Valeriy Shafiro; Stanley Sheft; Molly Norris; George Spanos; Katherine Radasevich; Paige Formsma; Brian Gygi (PLoS ONE, 2016)
Sounds in everyday environments tend to follow one another as events unfold over time. The tacit knowledge of contextual relationships among environmental sounds can influence their perception. We examined the effect of semantic context on the identification of sequences of environmental sounds by adults of varying age and hearing abilities, with an aim to develop a nonspeech test of auditory cognition.The familiar environmental sound test (FEST) consisted of 25 individual sounds arranged into ten five-sound sequences: five contextually coherent and five incoherent. After hearing each sequence, listeners identified each sound and arranged them in the presentation order. FEST was administered to young normal-hearing, middle-to-older normal-hearing, and middle-to-older hearing-impaired adults (Experiment 1), and to postlingual cochlear-implant users and young normal-hearing adults tested through vocoder-simulated implants (Experiment 2).FEST scores revealed a strong positive effect of semantic context in all listener groups, with young normal-hearing listeners outperforming other groups. FEST scores also correlated with other measures of cognitive ability, and for CI users, with the intelligibility of speech-in-noise.Being sensitive to semantic context effects, FEST can serve as a nonspeech test of auditory cognition for diverse listener populations to assess and potentially improve everyday listening skills.